Love and Romantic Relationships in the Voices of Patients Who Experience Psychosis: An Interpretive Phenomenological Analysis - Budziszewska, Magdalena Daria; Babiuch-Hall, Małgorzata; Wielebska, Katarzyna (Frontiers in Psychology, 2020)
Love is a universal experience that most people desire. A serious, long-term, and stigmatized illness makes entering and maintaining close relationships difficult, however. Ten persons, who have been diagnosed with schizophrenia, and lived with their illness for between years and decades of their lifetimes, shared their stories. They reported how the illness has influenced their emotional experiences regarding love and their intimate relationship experiences. We present here a qualitative Interpretative Phenomenological analysis (IPA) of their narratives. This analysis has been done with an explicit intention to give voice to the patient’s perspective. The results highlight how illness adjustment and hospitalizations have an alienating effect on relationships through stigmatization and self-stigmatization; how illness creates psychological obstacles to love, such as diminished trust toward oneself and others; and how long-term patients experience practical difficulties in creating and sustaining relationships, such as poverty. Moreover, we show how patients experience changes in sexuality and the risks involved in it, and discuss possible coping strategies from their perspectives.